Spontaneous regression of quiescent gestational trophoblastic disease after pregnancy: a case report - Yoshiyuki Okada; Shingo Miyamoto; Takashi Mimura; Tetsuya Ishikawa; Akihiko Sekizawa; Koji Matsumoto (BMC, 2019)
Abstract Background A persistent low-level elevation of serum human chorionic gonadotropin (hCG) without clinical or radiological evidence of pregnancy or tumors was recently defined as quiescent gestational trophoblastic disease (Q-GTD). Whether patients with Q-GTD should be treated or allowed to become pregnant remains unclear. We herein report a rare case of Q-GTD in which the hCG level spontaneously returned to normal after a successful pregnancy. Case presentation The patient was a 37-year-old primigravida who presented with a persistent low-level elevation of hCG after uterine evacuation of a hydatidiform mole. There was no evidence of neoplasia in the uterus or distant metastasis. The low-level elevation of hCG persisted for at least 2 years but never exceeded 200 mIU/mL. The patient had a successful pregnancy at the age of 40 years. Conclusions Interestingly, her hCG level subsequently normalized without chemotherapy. The present case may imply the safety and therapeutic effect of pregnancy in women with Q-GTD.